Utilization of Abandoned Land Based on Regulation of the Minister of Environment and Forestry Number 07 of 2021 for Food Estate - Rubby Aditya Panglima; Gunardi Lie (International Journal Labs, 2023)
Basic Agrarian Law no. 5 of 1960 stipulates that all land rights must have a social function, by Article 6 which states that land cannot be used solely for personal interests, especially if this is detrimental to society. Land use must be adapted to conditions and rights, providing benefits both for the owner & for the community and state. Abandoned land, including land rights, Management Rights, and land based on a Land Tenure Basis that is not used or cultivated, is the focus of this research. This research aims to explain the relationship between the 1960 Basic Agrarian Law regarding abandoned land and its derivative regulations, especially in the context of the National Food Estate Strategic Program. The research method uses secondary data with a normative juridical approach to synchronize legal provisions with field practice. Social Function is identified as an integral element in Land Rights, and the author believes that abandoned land, such as Cultivation Rights, can be used for the prosperity of the people. However, Minister of Environment and Forestry Regulation no. 07 of 2021 indicates that these social functions have not been fully utilized along with other land uses, creating inconsistencies in the implementation of the policy.